Cloud Computing - Haq, Hafiz (My University, 2013)
In the recent years, Cloud Computing has become very popular and an interesting subject in the field of science and technology. The research efforts in the Cloud Computing have led to a number of applications used for the convenience in daily life. Cloud Computing is not only providing solutions at the enterprise level but it is also suitable in organizing a centralized database which is accessible from every corner of the world. It is said that, 10 to 15 years later when all the enterprises have adopted the Cloud Computing, there will be no more perception for the data center in the company. The aim of this Master’s thesis “Cloud Computing: Server Configuration and Software Implementation for the Data Collection with Wireless Sensor Nodes” was to integrate the Wireless Sensor Network with Cloud Computing in a such a way that the data received from the Sensor node can be access able from anywhere in the world. To accomplish this task, a Wireless Sensor Network was deployed to measure the environmental conditions such as Temperature, Light and the Sensor’s battery information and the measured values are sent to a web server from where the data can be accessed. The project also includes the software implementation to collect the sensor’s measurements and a Graphical User Interface (GUI) application which reads the values from the sensor network and stores it to the database.
Keywords: GUI application; Sensor node.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|